The, of, in, the, of, from, the The Position of Murtad's Widow in the Distribution of Inheritance from the Testator (Husband) - Qisthina Armalia Hirzi; Ani Setiawati; Afdol (Fakultas Hukum Universitas Hang Tuah, 2020)
The research with the title of